Evaluation of Drainage Channels Capacity in Ambon City: A Case Study on Wai Batu Merah Watershed Flooding. (2015) - Kusumastuti, Cilcia; Djajadi, Ruslan; Rumihin, Angel
Abstract: Failure of urban drainage capacity to flow surface runoff due to rainfall is possibly to be a factor from many other factors causing flood in urban areas. Big floods in Ambon in 2013 which caused economic loss and loss of human life are the background to conduct a research which is presented in this paper. Ambon is the capital of Maluku Province located in Eastern Indonesia. Recently, the area of the city is developed into settlement area. The research is specifically conducted in Wai Batu Merah Watershed, a watershed in Ambon which severely damage due to floods in 2013. The analysis emphasizes on evaluation of capacity of existing drainage channels (natural and human-made). Daily rainfall data from Pattimura station during 2004 – 2013 is used to be the main data to estimate design rainfall and design flood. Design rainfall is the main data of rainfall-runoff model which is done using Synthetic Unit Hydrograph of SCS. While the fluctuation of water level along the main river is simulated using unsteady flow analyses with an input of 50-year design flood. The result of the simulation shows that one existing tertiary drainage channel cannot accommodate discharge of overland flow and from the upstream to the downstream of Wai Batu Merah River is overflow. Particularly on flood event in 2013, consecutive rainy days occurred since in the beginning of July until mid-August with total depth of rainfall more than triple of 50-year return period of maximum daily rainfall. At that state, flood certainly cannot be avoided in the adjacent area of the river.